Transient heat flux estimation during the baking of cereal batter by contact heating. (July 2020) - Marc, S.; Ploteau, J.-P.; Le Bideau, P.; Glouannec, P.
Highlights: The aim of this study is to estimate heat flux exchanged between two materials in contact at two different temperatures. The prescribed method is based on solving an IHCP from temperatures measurements judiciously located. The procedure is tested by numerical and experimental studies conducted for the heating of an elastomer plate and the baking of a cereal dough. The results show the ability of the method to estimate accurately heat flux which are time-dependent and highly variable. Abstract: In many applications, it is essential to evaluate the heat flux transferred by contact between two materials. Heat flux sensors must be properly designed to reduce sources of measurement bias while maintaining a high sensitivity without disrupting the flux itself. The aim of this study is to estimate the heat flux exchanged between two materials in contact at different temperatures. When materials are rapidly brought into contact (less than one second) the heat flux exchanged presents large variations. In this study, the heat fluxes transferred are computed using an inverse heat conduction problem. Initially, a particular attention is focused on the numerical analysis of the method and its reliability. A first experimental study is conducted on a prototype where an elastomer plate is suddenly placed on a hot iron disk. Based on temperature measurements recorded in each medium, the heat flux exchanged is estimated by two ways and the results are compared with each other. These first results show the efficiency of the method and its ability to extract information from temperature measurements. Then, a second experimental study is carried out with a cereal batter spread on the iron disk. The estimation of the heat flux from cast iron temperatures is compared with that deduced from an energy balance performed on the batter. The energy balance takes into account the sensible heat, the mass losses and the heat flux exchanged by radiation and convection with ambiance.